PERTANGGUNGJAWABAN PIDANA TERHADAP DOKTER ATAS KESALAHAN DAN KELALAIAN DALAM MEMBERIKAN PELAYANAN MEDIS DI RUMAH SAKIT - Erdiansyah ' (Fakultas Hukum Universitas Riau, 2013)
Disadvantaged communities on theneed of protection of medicalmalpractice law has resulted infurther harm or suffering to patients.To create a form of legal certaintyand ensure the health and serviceefforts to accommodate the needs ofthe government in addition to theCriminal Code have passed laws inthe fields of healthcare and physicianpractices legislation, namely Law No.23 of 1992 Jo Act No. 36 of 2009 onHealth and Law Number 29 Year2004 on Physician Practice. Criminalliability on doctors for errors andomissions in providing medicalservices at the hospital, wheredoctors responsibility in the field ofcriminal law can be categorized as acriminal act if they meet theformulation Malpractice criminaloffense.Kata Kunci:Pertanggung jawaban-Pidana-Kesalahan-Pelayanan-Medis